Stomatal Conductance of Potato Grown under Sub-tropical Conditions - De, Biman; Ghosh, Mayukh; Das, Banani; Das, Bimal (International Journal of Bio-resource and Stress Management, 2014)
Production of potato (Solanum tuberosum L.) under sub-tropical conditions may be feasible. However, suitable cultivars need to be evaluated to maximize yield. A characteristic that could be used to identify superior cultivars is high stomatal conductance. A field experiment was carried out at the institutional farm of Uttar Banga Krishi Viswavidyalaya, Pundibari, Cooch Behar, West Bengal, India, from November to February of 2006-2007 and 2007-2008 to determine how stomatal conductance, and other factors, affected yield of potato. The cultivars Kufri Pukhraj (V1), TPS 92 PT 27 (V2), Kufri Ashoka (V3), HPS II/13 (V4), Kufri Jyoti (non-certified, after 6th generation of V8; locally available from the plain source of Dhupguri) (V5), Kufri Chipsona 2 (V6), Kufri Chandramukhi (V7), Kufri Jyoti (certified seed, hill source cultivar of Solan) (V8), Local Cultivar (V9) and Kufri Jyoti (2nd generation saved seed of V8) (V10) were used. Yield of Kufri Jyoti (V8) had among the highest stomatal conductance, internal humidity and internal CO2 levels in leaves. Kufri Jyoti (V8) had the highest tuber bulking and final tuber yield followed by Kufri Pukhraj and 92 PT 27. Stomatal conductance can be used as a criterion to identify potato cultivars suited for production under sub-tropical conditions.